Can Complex 3D Models Effectively Replace 2D and Animal Models to Investigate the Microbe-Tumor-Immune Axis in Pancreatic Cancer Studies? - Ozeer, Fathima Zahraa; Kester, Jemila Caplan (MDPI AG, 2026)
The tumor microbiome has been implicated in pancreatic ductal adenocarcinoma (PDAC)’s poor response to treatment, demanding new methods for understanding host-microbe interactions in therapy. Traditional 2D systems, while widely used, fail to adequately recapitulate human PDAC due to insufficient representation of structural, immunological and stromal components. Differences in cancer-specific microbiomes, microbe-immune interactions, and the unique physiological and immunosuppressive features unique to PDAC have hindered the clinical translation of immune therapies. Reproducible 3D culture systems that integrate the human microbe-tumor-immune (MTI) axis represent a promising avenue for treatment research, yet they remain underexplored in PDAC. In this narrative review, we discuss the key microbial determinants of therapy resistance, explore the current 3D multicellular modeling approaches in other cancer types, and provide a path forward for similar integrative translational models in PDAC.
Keywords: 0908 Food Sciences; 1111 Nutrition and Dietetics; 3202 Clinical sciences; 3210 Nutrition and dietetics; 4206 Public health; pancreatic cancer; immune checkpoint inhibitor; organoids; spheroids; microbiomes